المحررات الإلكترونية كدليل إثبات - براهمي, حنان (revue mofakir, 2018)
Thanks to the new technologie there was an access to the électronic goverment which led to a change of the old system of documents to the new one which is the electronic documents.  All that made the alteration of the document’s definition which led us to recheck its own legal organization especially the evedential value on the local and the international level . The features the electronic documents have ; however,made it equivalent to the paper documents concerning the evedential value and this is what leads all legeslations to work with this document. إن الدخول إلى نظام الحكومة الإلكترونية ، و رقمنة الإدارة بفضل التكنولوجيا الحديثة أدى إلى تحول المحررات الورقية إلى محررات الكترونية في التعاملات الخاصة أو الحكومية . لقد أدى هذا إلى تغير مفهوم المحرر مما أدى إلى إعادة النظر في النظام القانوني الخاص به، من حيث القيمة القانونية له في الإثبات سواء على المستوى الدولي أو المحلي . ويتمتع المحرر الإلكتروني بمجموعة من الخصائص جعلته يساوي المحرر الورقي من حيث القيمة الثبوتية ، و هذا ما تتجه إليه أغلب التشريعات لضمان التعامل به .